Effectiveness versus efficacy trials in COPD: how study design influences outcomes and applicability. Issue 2 (22nd February 2018) - Woodcock, Ashley; Boucot, Isabelle; Leather, David A.; Crawford, Jodie; Collier, Susan; Bakerly, Nawar Diar; Hilton, Emma; Vestbo, Jørgen
Guidelines for chronic obstructive pulmonary disease (COPD) management are based largely on results from double-blind randomised controlled trials (RCTs) of efficacy. These trials have high internal validity and test whether a drug is efficacious, but they are conducted in highly selected populations that may differ significantly from patients with COPD seen in routine practice. We compared the baseline characteristics, healthcare use and outcomes between the Salford Lung Study (SLS), an open-label effectiveness RCT, with six recent large-scale efficacy RCTs. We also calculated the proportion of SLS patients who would have been eligible for inclusion in an efficacy RCT by applying the inclusion criteria used in efficacy trials of combination treatments. SLS patients were older, included more females and more current smokers, had more comorbidities (including asthma), and had more often experienced exacerbations prior to inclusion. In the SLS, rates of moderate or severe exacerbations, incidence of overall serious adverse events (SAEs), and SAEs of pneumonia were more frequent. A maximum of 30% of patients enrolled in the SLS would have been eligible for a phase IIIa regulatory exacerbation study. Patients in large COPD efficacy RCTs have limited representativeness compared with an effectiveness trial. This should be considered when interpreting efficacy RCT outcomes and their inclusion into guidelines. Efficacy trials are less representative than effectiveness trials and both are required when evaluating treatments http://ow.ly/plwd30he4a2